IMPROVED DYNAMIC BOTANICAL AIR PURIFIER WITH LIGHT EFFECT FOR REDUCING CO2 CONCENTRATION IN CHAMBER - Carolina Dwi Sundari; Muhammad Fajri Hadi Syahputra; Lulu Millatina Rachmawati; Andhika Jalasena; Nabil Ananta Hasmul; Indra Chandra; Rahmat Awaludin Salam; Yeni Octaviani; Zahwa Rizzi Ani; Sefani Fitria Suyatna; Azrina Abd Aziz; Zainal Arif Burhanudin (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2024)
Aims: This study aimed to investigate the effectiveness of the DBAP in reducing CO2 levels and improving indoor air quality. It also explores the impact of adding blue light to enhance photosynthesis. Additionally, the study examines the ability of the DBAP's HEPA filter to reduce PM2.5 concentration. Methodology and results: The methodology used in this study involved testing the reduction of CO2 levels in plants using blue light as an enhancement. The researchers also developed a Dynamic Botanic Air Purifier (DBAP) that incorporated activated carbon and a fan as an active filter to improve CO2 reduction. The study measured the reduction level of CO2 in the plants with blue light enhancement, resulting in a 40% reduction. Subsequently, after adding the active filter to the plants, the CO2 reduction improved by an additional 11% compared to without the active filter. Additionally, the study found that the HEPA filter within the active filter effectively reduced the concentration of PM2.5 to 71.6%. Conclusion, significance and impact study: In conclusion, this study highlights the significance of addressing poor indoor air quality and its potential impact on occupant health and well-being. Developing the Dynamic Botanic Air Purifier (DBAP), incorporating plants, activated carbon, a fan, and blue light enhancement, offers a promising solution for improving indoor air quality and preventing Sick Building Syndrome (SBS). The findings of this study have the potential to inform the development of effective strategies and technologies aimed at creating healthier indoor environments, thus positively impacting public health and overall indoor air quality.